Landing kinematics in elite male youth soccer players of different chronologic ages and stages of maturation - Read, P. J.; Oliver, J. L.; De Ste Croix, M. B. A.; Myer, G. D.; Lloyd, R. S. (Journal of Athletic Training, 2018)
Context: Despite the high frequency of knee injuries in athletes, few researchers have studied the effects of chronologic age and stage of maturation on knee-joint kinematics in male youth soccer players.